If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -6y + -4 = 68.95 Reorder the terms: -4 + 11y + -6y = 68.95 Combine like terms: 11y + -6y = 5y -4 + 5y = 68.95 Solving -4 + 5y = 68.95 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5y = 68.95 + 4 Combine like terms: -4 + 4 = 0 0 + 5y = 68.95 + 4 5y = 68.95 + 4 Combine like terms: 68.95 + 4 = 72.95 5y = 72.95 Divide each side by '5'. y = 14.59 Simplifying y = 14.59
| -5=3t | | 15=4.3m-2.1(m-4) | | (2x-5)(x+4)-20=0 | | 3x+7=-1x+(-3) | | x-6=(-18) | | 3x+2+5(x-1)=8+17 | | a[n]=5n-1 | | (2-7y)-3(y-9)= | | -4y=26-27 | | 3+x=(3x-9) | | 3x+7=-1x+-3 | | -8x=-4x-20 | | -5x+30=-20x | | 0.04(42)+0.16x=0.08(x+42) | | -2500+(-200x)=5100 | | 2r^2+3r-3=0 | | 3x+7=-1x-3 | | 7(7-8k)+3(k-5)= | | 121x^2-64=0 | | 110-(-50)=n | | (4-x)+(2x+5)= | | X(X-5)=2x-10 | | -50+n=110 | | 4(x-1)=5(2x+3) | | 10.50+8.25(h-1)=34 | | -2z=-4 | | 4(2-4k)+8(7k-1)= | | 6x^2+4x=3x^2-5x | | 18u-24-9u=6u-36-3 | | 6y+4=2(y-2) | | 2-39x+40=8 | | (2x-5)(x+4)+20=0 |